SURGICAL REVISION OF VENTRICULOPERITONEAL SHUNT IN HYDROCEPHALUS PATIENTS WITH INTRACRANIAL TUMORS (Iraqi Journal of Medical Sciences, 2016)
Background:Patients with intracranial tumors are predis¬posed to persistent hydrocephalus, often requiring a per-manent CSF diversion procedure with shunts.Objective:This study reviews the long-term experience with ventriculoperitonealshunts for the management of hydrocephalus in patients with intracranial tumors.Methods:Patients with intracranial tumors who underwent ventriculoperitoneal shunt placement for hydrocephalus from January 1999 to January 2009 were included in this study from four neurosurgical centers in Baghdad/Iraq. During the 10-year period, medical charts, operative reports, imaging studies, and clinical follow- up evaluations were reviewed and analyzed retro¬spectively for all patients. A total of 187 intracranial tumor patients with hydrocephalus were included. The median follow up was 391 days. Malignant tumors were present in 40% of the patients.Results:Overall shunt failure was 27.8%. Single shunt revision occurred in 13% of the patients and 14% had multiple shunt revision. Tumor histology, age and a procedure prior to shunt placement (ventriculostomy/ Ommaya reservoirs) were significantly associated with the shunt revisions. Shunt system replacement and proximal shunt complication were significantly attributed to multiple shunt revisions. The overall shunt revision within 3 months, 6 months, 1 year and 2 years was 17.7%, 18.7%, 19.8% and 24.1%, respectively.Conclusions:The results of the studydemonstrate that VP shunting is an effective procedure for the man¬agement of hydrocephalus in patients with intracranial tumors. Age, tumor histology, and a procedure prior to shunt placement (ventriculostomy/Ommaya reservoirs) were significantly associated with the shunt revisions.Key words:Brain neoplasm, Cerebrospinal fluid, Surgery, Shunt
Keywords: Brain neoplasm; Cerebrospinal fluid; Surgery; Shunt